PENGGUNAAN MODEL PEMBELAJARAN â€œBTLâ€ (BETTER TEACHING AND LEARNING) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATA PELAJARAN IPS PADA PESERTA DIDIK KELAS VIII SMP NEGERI 2 DEMAK TAHUN PELAJARAN 2015/2016 - Karsidi, Karsidi (Universitas Negeri Semarang, 2015)
This research aimed to evaluate learning model â€œBetter Teaching and Learning (BTL)â€ in improvingacticities and learning result of VIII grade students of J class in SMP N 2 Demak study year 2015/2016. Itwas a Classroom Action Research which consist of Planning, Acting, Observing, and Reflecting. Datacollection methods were documentation, observation, and writing test. Data analysis method used interactivemodel of Miles and Huberman, which consist of data reduction, data presentation, and verification.This research showed that BTL method usage could increase activities and result of social science study inthe research object. Learning activity from the beginning was 62, average result after the first cycle was 75,and after the second cycle was 94. In other word, there was point increasement till 51%. In the same way,there was an improvement too in learning result, from 70 become 75 in the first cycle, and 88 after thesecond cycle, which mean that the score increased 25%. Therefore, the BTL method should be develop inother material learning. Colleagues need to review this method, than develop it within learning process.